Boom Chack Boom—A multimethod investigation of motor inhibition in professional drummers. Issue 1 (4th December 2019) - Schlaffke, Lara; Friedrich, Sarah; Tegenthoff, Martin; Güntürkün, Onur; Genç, Erhan; Ocklenburg, Sebastian
Abstract: Introduction: Our hands are the primary means for motor interaction with the environment, and their neural organization is fundamentally asymmetric: While most individuals can perform easy motor tasks with two hands equally well, only very few individuals can perform complex fine motor tasks with both hands at a similar level of performance. The reason why this phenomenon is so rare is not well understood. Professional drummers represent a unique population to study it, as they have remarkable abilities to perform complex motor tasks with their two limbs independently. Methods: Here, we used a multimethod neuroimaging approach to investigate the structural, functional, and biochemical correlates of fine motor behavior in professional drummers ( n  = 20) and nonmusical controls ( n  = 24). Results: Our results show that drummers have higher microstructural diffusion properties in the corpus callosum than controls. This parameter also predicts drumming performance and GABA levels in the motor cortex. Moreover, drummers show less activation in the motor cortex when performing a finger‐tapping task than controls. Conclusion: In conclusion, professional drumming is associated with a more efficient neuronal design of cortical motor areas as well as a stronger link between commissural structure and biochemical parameters associated with motor inhibition. Abstract : Our multimethodal MRI data provide evidence that professional drumming is associated with a more efficient neuronal design of cortical motor areas, as well as a stronger link between commissural structure and biochemical parameters associated with motor inhibition. This shows that long‐term learning of complex motor tasks could lead to substantial restructuring in cortical motor networks, which could also have interesting implications for clinical applications for patients with motor disorders.